Physicochemical properties and biological interaction of calcium silicate-based sealers - in vivo model - Janini, Ana Cristina Padilha; Moraes, Brenda Fornazaro; Pelepenko, Lauter Eston; dos Santos, Victor Augusto Benedicto; Barros-Costa, Matheus; Malosá, Gabriela Fernanda; Batista, Fábio Roberto de Souza [UNESP]; Meira, Juliana de Aguiar Silveira [UNESP]; Matsumoto, Mariza Akemi [UNESP]; Antunes, Thiago Bessa Marconato; Darin Filho, Gaspar; Haiter Neto, Francisco; et al. (Springer Nature, 2025)
Objectives: To investigate volumetric changes, in vivo biocompatibility, and systemic migration from eight commercial endodontic sealer materials in paste/paste, powder/liquid, and pre-mixed forms. Materials and methods: The sealers AH Plus Bioceramic, AH Plus Jet, BioRoot RCS, MTApex, Bio-C Sealer, Bio-C Sealer Ion+, EndoSequence BC Sealer and NeoSEALER Flo were studied. After characterisation by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), Raman spectroscopy and X-ray diffractometry (XRD), tubes were implanted in Wistar rats’ alveolar bone and subcutaneous tissues. Micro-CT evaluated volumetric changes pre/post 30 days of implantation. Histological and immunohistochemistry analyses assessed biocompatibility. Kidney samples underwent spectrometry (ICP-MS) for tantalum, tungsten and zirconium. Statistical analysis determined normality and significance (udp < 0.05). Results: Characterisation revealed calcium, silicon, and radiopacifiers in the materials. Volumetric changes showed greater alteration in subcutaneous tissues than alveolar bone; BioRoot RCS and MTApex (powder/liquid) were most stable. Histological analysis indicated intense inflammation for AH Plus Jet, moderate for others; IL-10 was marked positively for all materials. AH Plus Jet had an 18-fold higher tungsten and a 37-fold higher zirconium mass fraction in kidneys versus controls, while tantalum showed lower accumulation patterns. Conclusion: Root canal filling materials’ responses varied by implantation site and form, demonstrating acceptable biocompatibility. Tantalum and zirconium oxide radiopacifiers appear systemically safe; tungsten-based radiopacifiers are unsuitable due to metal accumulation risks. Clinical Relevance: This study highlights the need for further in vivo studies on endodontic sealers’ chemical, biological, and physical behaviors and their systemic migration.
Keywords: Biocompatibility; Endodontics; Root canal filling materials; Systemic migration; Volumetric change; Wistar rats